Hereditary transthyretin-related amyloidosis is frequent in polyneuropathy and cardiomyopathy of no obvious aetiology. (1st January 2021) - Skrahina, Volha; Grittner, Ulrike; Beetz, Christian; Skripuletz, Thomas; Juenemann, Martin; Krämer, Heidrun H.; Hahn, Katrin; Rieth, Andreas; Schaechinger, Volker; Patten, Monica; Tanislav, Christian; Achenbach, Stephan; et al.
Abstract: Background: Hereditary Transthyretin-Related Amyloidosis, a clinically heterogeneous autosomal dominant disease caused by pathogenic variants in the TTR gene, is characterized by the deposition of insoluble misfolded protein fibrils. The diagnosis, especially in non-endemic areas, is typically delayed by 4–5 years; a misdiagnosis due to clinical heterogeneity is common. The study objective was to define the prevalence of Hereditary Transthyretin-Related Amyloidosis in patients with polyneuropathy and/or cardiomyopathy of no obvious aetiology. Method: A multicenter observational "Epidemiological analysis for the hereditary Transthyretin-Related AMyloidosis"—TRAM study was performed in Germany, Austria, and Switzerland. Results: A total of 5141 participants were recruited by 50 neurologic and 27 cardiologic specialized centres. Genetic analysis demonstrated a 1.1% Hereditary Transthyretin-Related Amyloidosis positivity rate among patients with polyneuropathy and/or cardiomyopathy of not obvious aetiology. Twenty-one various TTR variants ( TTR -positive) were identified. Body Mass Index was lower in the TTR -positive patients as an indicator for the involvement of the autonomic nervous system; the age of onset of clinical manifestations was higher in TTR -positive patients. There were no other genotype-phenotype correlations or the prevalence of specific clinical manifestations in TTR -positive patients. Conclusions: Our data support the fact that Hereditary Transthyretin-Related Amyloidosis is underdiagnosed in polyneuropathy and cardiomyopathy patients. Routine implementation of genetic testing is recommended in patients with unexplained polyneuropathy and/or cardiomyopathy to accelerate the earlier diagnosis and the time-sensitive treatment initiation. KEY MESSAGES: More than 5.000 participants with CM and/or PNP of no obvious aetiology were recruited in the observational "Epidemiological analysis for the hereditary Transthyretin-Related AMyloidosis" TRAM study and screened for pathogenic TTR variants. The study demonstrated >1% of patients with CM and/or PNP of unclear aetiology are positive for a pathogenic TTR variant. Routine genetic testing is recommended in patients with unexplained CM and/or PNP to accelerate the initial diagnosis and timely treatment initiation.